BEMP-Promoted C(4)-Alkylation of 4-Alkyloxazol-5(4H)-ones: A Rapid and Efficient Route to α,α-Dialkyl-α-amino Acids - Lee, Yeon-Ju; Seo, Jeyoung; Kim, Dong-Guk; Park, Hyeung-geun; Jeong, Byeong-Seon (Synlett, 2013)
Rapid and efficient C(4)-alkylation of 4-alkyloxazol-5(4H)-ones has been achieved by the utilization of BEMP as base. 4,4-Dialkyloxazol-5(4H)-ones, which can easily be hydrolyzed into free α,α-dialkyl-α-amino acids, were obtained in high yields (up to 99%) within a few minutes (1–18 min). BEMP, a sterically hindered strong base with low nucleophilicity facilitated the desired reaction, while decreasing the rate of side reactions such as O-alkylation, C(2)-alkylation and the breakage of oxazolone.
Keywords: α,α-dialkyl-α-amino acid; oxazol-5(4H)-one; C(4)-alkylation; BEMP; protecting group; chemoselectivity